A comprehensive study of three high‐gain DC‐DC topologies based on Cockcroft‐Walton voltage multiplier for reduced power PV applications. Issue 4 (18th January 2018) - Abdel‐Rahim, Omar; Funato, Hirohito; Haruna, Junnosuke
Abstract : This work provides a comprehensive study of three different topologies founded on the well‐known Cockcroft–Walton (CW) voltage multiplier for reduced power PV Applications. A comprehensive study and investigational outcomes of each converter are offered, and a detailed comparison among the three topologies is performed. The three topologies target AC module technology application, where every PV unit consumes its identifiable DC–DC converter. In AC PV module technology, PV generated‐voltage is fit for 30 V, and the available sum of power is less than 200 W. Converters for PV use are required to have great step‐up ability and higher efficiency as a result of the reduced output voltage of PV. The three topologies have some common benefits like high step‐up abilities and moderate efficiency. The three topologies are so‐called Switched‐Inductor with Voltage Multiplier (SIVM), high gain with voltage multiplier and Z ‐Source with voltage multiplier (ZSVM). © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.